Quality controls for CBCT devices: The efomp guideline for quality assurance of images and dose. (September 2016) - las Heras, H.; Rampado, O.; Andersson, J.; Giron, I. Hernandez; Nilsson, M.; Dasu, A.; Holroyd, J.; Theodorakou, C.; Torresin, A.
Abstract : Introduction: Current guidelines for quality control of CBCT devices consider the available applications (dental, radiotherapy, interventional radiology and guided surgery) as different entities. However, the data acquisition and reconstruction methods are similar. Henceforth, the evaluation parameters for image quality and dose can be unified. Purpose: The purpose of this guideline (under discussion since January 2014 within an EFOMP working group) is to present an objective, practical and unifying procedure for quality control of all imaging CBCT applications Materials and methods: The parameters used for image quality assessment are uniformity, accuracy of density values (or Hounsfield units where appropriate), geometrical evaluation, noise, low contrast resolution (including contrast to noise ratio) and high contrast resolution. Results: Detailed procedures using free software and commercially available test phantoms are described. The dosimetric quantities under consideration are CTDI, kerma area product and detector incident air kerma. Recommended action levels and test frequency are indicated together with references wherever possible. Conclusion: This guideline includes the minimum tests that should be performed to ensure reliable, safe and consistent performance of CBCT devices. This minimum has been sought to guarantee compatibility with all manufacturers and existing European documents (DIN 6868161, HPACRCE010 and RP 172 for dental applications). Disclosure: Nothing to disclose.